Periodontal Disease Is Associated With Increased Risk of Hypertension: A Cross-Sectional Study - Zhao, Ming-Juan; Qiao, Yi-Xin; Wu, Lan; Huang, Qiao; Li, Bing-Hui; Zeng, Xian-Tao (Frontiers in Physiology, 2019)
Objective: Published evidence showed that periodontal disease is associated with hypertension. However, relevant findings remain controversial, with few evidences focusing on Chinese population. Therefore, the aim of this study was to investigate the association between periodontal disease and hypertension in Chinese population. Methods: A total of 4,930 participants from an available health examination that was carried out in 2017 were selected for this retrospective study. The correlations between periodontal disease and hypertension were investigated using univariate and multiple logistic regression analyses and propensity score adjusted analysis. Interaction and subgroup analyses were also used to detect variable factors. Results: Finally, a total of 3,952 participants aged 30–68 years were eligible for this study. The results showed that hypertension risk was statistically significant associated with periodontal disease either in unadjusted (OR = 1.28, 95%CI = 1.14–1.47) or in adjusted (OR = 1.34, 95%CI = 1.14–1.58) model. Result from propensity score adjusted analysis also demonstrated a similar association (OR = 1.23, 95%CI = 1.06–1.42). Conclusion: Periodontal disease is significantly and positively correlated with increased risk of hypertension in Chinese population, and exact mechanisms of this association should be explored in future.